Comparison of Essential Oils of Houttuynia cordata Thunb. from Different Processing Methods and Harvest Seasons Based on GC-MS and Chemometric Analysis - Xue Pan; Haiying Li; Dingfang Chen; Jinjin Zheng; Longhua Yin; Juan Zou; Yalun Zhang; Kaiwen Deng; Meifeng Xiao; Lei Meng; Fuyuan He (International Journal of Analytical Chemistry)
Houttuyniae Herba (HH) refers to the dried aerial part of Houttuynia cordata Thunb. (DHC) or the fresh whole grass of Houttuynia cordata Thunb. (FHC), where DHC are harvested in summer and FHC around the year. However, harvest seasons and processing methods (i.e., medicinal parts and drying process) might affect the quality of HH. To compare the essential oils (EOs) of DHC and FHC and their two harvest seasons, GC-MS analysis combined with chemometric analysis was applied. The results showed that the oil yield of FHC (0.076 ± 0.030%) was higher than that of DHC (0.038 ± 0.029%), and oil yield was higher in summer than in autumn (0.044 ± 0.029% for DHC1, 0.036 ± 0.028% for DHC2, 0.084 ± 0.026% for FHC1, and 0.067 ± 0.033% for FHC2, respectively). Moreover, hierarchical cluster analysis (HCA) and principal component analysis (PCA) successfully distinguished the chemical constituents of DHC and FHC oils. Additionally, according to orthogonal partial least squares discriminant analysis (OPLS-DA), eleven components were selected as chemical markers for discriminating DHC and FHC, and two and four chemical markers for discriminating two harvest seasons of DHC and FHC, respectively. Among these markers, the average contents of α-pinene, limonene, β-phellandrene, α-terpineol, 4-tridecanone, and ethyl decanoate were higher in FHC oils. In contrast, the average contents of nonanal, 1-nonanol, β-cyclocitral, n-hexadecanoic acid, and octadecanol were higher in DHC oils. Additionally, the contents of 4-tridecanone and ethyl decanoate were both higher in DHC1 oils than in DHC2 oils. Moreover, the contents of β-myrcene and β-phellandrene were higher in FHC1 oils, while the contents of 2,6-octadien-1-ol, 3,7-dimethyl-, acetate, and (z)-phytol were higher in FHC2 oils. For these reasons, this study provides a scientific basis for quality control and clinical medication.